Eradication, elimination and control of neglected tropical diseases - Molyneux, CMG, David (Henry Stewart Talks, 2019)
International task force for disease eradication, Definition of ‘eradication’, ‘elimination’, and ‘control’ of neglected tropical diseases, Eradication and elimination are long term commitments, Examples of NTDs, Biological, socio-geographic, political, resource constraints, and conflict in NTD management, Examples of therapeutics used against NTDs